Relações de concordância verbal envolvendo as variantes nós e a gente no português brasileiro: uma proposta didática - Lima, Fábio Ronne de Santana (2022)
This research aims to present a didactic proposal based on the variable behavior of verbal agreement relations involving the first person plural (CV of 1PP), nós and a gente, in the production of written texts by 8th and 9th grade students. Elementary School and the 2nd and 3rd year of High School. Therefore, we present theoretical-methodological reflections about the multi-theoretical need required for the teaching of language and grammar. As a guideline, we support the discussion based on culturally sensitive pedagogy, the pedagogy of linguistic variation (BORTONI-RICARDO, 2009 [2004]; 2005; 2017; FARACO, 2015), and we take advantage of the proposal of teaching grammar in three axes (VIEIRA , 2017a; 2017b; 2017c). In the theoretical-methodological aspect, we carried out a quantitative qualitative research, of an applied nature, under a dialectical approach, with an action research method, anchored by the analysis of variationist sociolinguistics (LABOV, 2008 [1972]) and educational sociolinguistics (BORTONI -RICARDO, 2009 [2004]; 2005). As instruments, we used the writing production of 32 Basic Education students from the city of Juazeiro, Bahia. Each contributor created a personal letter and a letter of request. We submitted these data to statistical analysis, using the GoldVarb X program, and found that the variant nós, in the variable pronominal form, and the variant personal letter, in the variable textual genre, favored the maintenance of non-standard agreement. The didactic proposal that we built offers a block of commented activities, making use of the pedagogy of linguistic variation, whose purpose is the productive teaching of grammar and sociolinguistic reflection on the variants of the CV of 1PP, both in traditional grammar and in the varieties effectively in use.